Oral pleasure Kosinski as storyteller - Kosinski, Jerzy N. 1933-1991 (Grove Press, 2012)
A collection of interviews, lectures, and transcriptions of media appearances from the legendary literary figure, offering insight into his work and uncovering his personal history
A collection of 64 interviews, lectures, and transcriptions of media appearances, 1965-1990
Includes bibliographical references (p. 401-409)
On autobiography as fiction / fiction as autobiography -- On writing -- On storytelling -- On censorship -- On autofiction -- On Poland -- On the Holocaust -- On Jewish identity -- On world affairs -- On sex -- On television -- On acting -- On popular culture -- On "Being there" -- On violence -- On the American dream
Keywords: Kosinski, Jerzy / 1933-1991; Kosinski, Jerzy / 1933-1991 / Interviews; Kosinski, Jerzy N. -- 1933-1991; Geschichte 1900-2000; Novelists, American / 20th century / Interviews; Quelle